Detection of dsDNA with [1, 3]Dioxolo[4, 5‐f]benzodioxol (DBD) Dyes. Issue 60 (4th October 2018) - Büchner, Dörthe; John, Leonard; Mertens, Monique; Wessig, Pablo
Abstract: DBD fluorescent dyes have proven to be useful in numerous applications. To widen the range of biological applications, we propose three different types of DBD molecules that have been modified in such a way that DNA interaction becomes probable. After the successful synthesis of all three compounds, we tested their fluorescent properties and their DNA binding abilities. Two of the three probes exhibit an interaction with dsDNA with subsequent fluorescence enhancement. The determined binding constants of the two new DNA dyes are comparable to other minor‐groove‐binding dyes. Their large Stokes shifts and their long fluorescent lifetimes are outstanding features of these dyes. Abstract : DNA highlights : Two fluorescent dyes based on the DBD fluorophore have been developed that can be used to selectively detect dsDNA (see figure). Large Stokes shifts and long fluorescence lifetimes are outstanding features of these dyes.